Symbiotic Relationship between Deviant Religious Teachings and Conspiracy Theories: Characteristics, Adaptability, and Impact on the Muslim Community - Che Nordin, Mohd Khairul Naim (Online Journal of Research in Islamic Studies, 2023)
This paper examines the symbiotic relationship between deviant religious teachings and conspiracy theories, investigating their shared characteristics, adaptability, and impact on the Muslim community. The study objectives encompass analyzing examples of this relationship, exploring the factors driving the utilization of conspiracy theories by deviant teachings, and evaluating the consequences for the Muslim community. Employing a qualitative approach, the research integrates a comprehensive literature review, case study analysis, and examination of online sources. The analysis involves collecting and scrutinizing instances of deviant teachings and their utilization of social media platforms, along with the accompanying conspiracy theories. The roles played by conspiracy theories in fostering group cohesion, legitimizing teachings, mobilizing support, and countering criticism are assessed. The findings reveal the extensive exploitation of social media and the internet by deviant teachings to propagate their ideologies. Conspiracy theories serve as potent tools to augment the appeal and credibility of these teachings, contributing to the formation of group identities, the establishment of legitimacy, and the attraction of followers. Furthermore, the study uncovers indications of potential involvement of proponents of deviant teachings as conspirators, given the proliferation of teachings with unclear sources and the reliance on conspiracy theories. In conclusion, this study emphasizes the necessity of comprehending and addressing the symbiotic relationship between deviant teachings and conspiracy theories. By promoting informed religious education and leveraging social media effectively, it is feasible to mitigate the adverse impact of these ideologies and safeguard the Muslim community against misconceptions and divisive influences.